PREDICTION OF CUMULONIMBUS (CB) CLOUD BASED ON INTEGRATED FORECAST SYSTEM (IFS) OF EUROPEAN MEDIUM-RANGE WEATHER FORECAST (ECMWF) IN THE FLIGHT INFORMATION REGION (FIR) OF JAKARTA AND UJUNG PANDANG - Achmad Fahruddin Rais; Fani Setiawan; Rezky Yunita; Erika Meinovelia; Soenardi Soenardi; Muhammad Fadli; Bambang Wijayanto (BPPT, 2020)
This study was focused on cumulonimbus (Cb) cloud prediction based on Integrated Forecast System (IFS) European Medium-Range Weather Forecast (ECMWF) model in the Flight Information Region (FIRs) Jakarta and Ujung Pandang. The Cb cloud prediction was calculated using convective cloud cover (CC) of the precipitation product. The model predictability was examined through categorical verification. The Cb cloud observation was based on brightness temperature (BT) IR1 and brightness temperature difference (BTD) IR1-IR2. The results showed that CC 50%' predictor was the best predictor to estimate the Cb cloud. The study in the period other than 2019 is suggested for the next research because Indian Ocean Dipole (IOD) is extreme that may affect the Cb cloud growth in the study area.